Strategi Pengembangan Wisata Hutan Mangrove di Desa Budo Kecamatan Wori Kabupaten Minahasa Utara - Gumalang, Angely Brigitha; Lolowang, Tommy Ferdy; Memah, Melsje Jelly (Sam Ratulangi University, 2023)
This research aims to examine the strategy for developing Mangrove forest tourism in Budo Village, Wori District, North Minahasa Regency. This research was carried out for 2 months starting from May to June 2023. The sampling method in this research was purposive sampling and accidental sampling. The data used are primary data and secondary data. Primary data was obtained from direct interviews with 30 respondents and observations at the Mangrove forest tourist attraction in Budo Village, Wori District, North Minahasa Regency. Meanwhile, secondary data was obtained from the internet in the form of information or data related to the strategy for developing Mangrove forest tourism in Budo Village, Wori District, North Minahasa Regency. The research results show that based on the SWOT analysis, the Mangrove forest tourism development strategy is in quadrant I, meaning that a strategy is needed to support existing strengths and take advantage of various existing opportunities.